Analisis Pengaruh Mata Kuliah Statistik Untuk Penelitian Tugas Akhir Mahasiswa - Rini Ramadhani; Rizka Fahruza Siregar; Hetty Elfina (Journal on Education, 2024)
This research aims to analyze whether or not there is an influence of statistics courses on final assignment research in the sharia accounting department. The sampling technique used was a purposive sampling technique with the population being study syariah accounting at the North Sumatra State Islamic University (UINSU). This research uses a quantitative research method with primary data in the form of a questionnaire. Hypothesis testing uses simple linear regression analysis techniques. So the results obtained in the research show, with a significance level of 0.000 <0.05, (probability) meaning that the Statistics Subject has a significant effect on the final assignment research student university..